The THE NEOLIBERAL POLITICAL ECONOMY OF HIGHER EDUCATION: MARKETIZATION AND ITS IMPACT ON ACCESS AND QUALITY AT UNIVERSITAS HASANUDDIN - Esmati, Shahabuddin; Emynorane, Ralaivao Hanginiaina; Arrive, Jean Tsitaire (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to analyze the impact of neoliberal political economy in the context of higher education, precisely at Universitas Hasanuddin. The main focus of the study is to explore how the marketization process of higher education affects the accessibility and quality of education. The approach used in this study is qualitative with data collection methods through semi-structured interviews with 30 students and documentation studies related to the policies implemented at Hasanuddin University. The results show that the application of neoliberal principles in higher education management, such as an emphasis on efficiency, commercialization of educational services, and adapting the curriculum to market needs, has a significant impact on the accessibility of education for students from low economic backgrounds, as well as affecting the quality of education received. Apart from that, this marketization also has the potential to create inequality in the distribution of resources and create a gap between universities that have more funds and those that have less. It is hoped that these findings will provide deeper insight into the impact of neoliberal political economy on higher education and propose policies to improve access and quality of education at the state universities in Indonesia.